2021
DOI: 10.1016/j.cmi.2021.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of replacement of genetic variants of SARS-CoV-2 in association with containment capacity and changes in disease severity

Abstract: Objectives: To examine severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant replacement in association with containment capacity and changes in case fatality at country level. Methods: Altogether, 69 571 full SARS-CoV-2 genomes collected globally within the first 6 months of the pandemic were examined. The correlation between variant replacement and containment capacity was examined by logistic regression models using the WHO International Health Regulation (IHR) score, the Oxford COVID-19 Gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
(18 reference statements)
0
25
0
1
Order By: Relevance
“…By contrast, ORF1ab 4715L and S protein 614G variants were significantly more frequent in patients from countries where high fatality rates were also reported [8,10,11,57,59,60]. Patients infected with virus clades L, G and O were also exposed to a higher risk of severe infection than the base level [54].…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, ORF1ab 4715L and S protein 614G variants were significantly more frequent in patients from countries where high fatality rates were also reported [8,10,11,57,59,60]. Patients infected with virus clades L, G and O were also exposed to a higher risk of severe infection than the base level [54].…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 89%
“…Three studies (one bigdata analysis [50] and two clinical studies [17,51]) reported that the SARS-CoV-2 variants were significantly associated with decrease in severity of disease. The remaining 27 studies (one animal study [18], 22 bigdata analyses [8][9][10][11][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] and four clinical studies [70][71][72][73]) described the positive association between the different variants with severity of COVID-19 (Table 3). A clinical study by Long et al showed that infection with SARS-CoV-2 variants harboring the D614G substitution was not associated with disease severity, overall mortality, transfer to ICU, mechanical ventilation and length of stay at hospital [41].…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 99%
“…The displacement of SARS-CoV-2 lineage across each phase suggests that the new successive lineage had higher adaptive value than the last one [4,6]. Indeed, the three lineages progressively accumulated aggressive key mutations associated with higher transmissibility or evasion to the host immune system response: namely, B.1.1.33 carried D614G, P.2 harbors D614G and E484K, and P.1 carries N501Y in addition to the two previous mentioned.…”
Section: Discussionmentioning
confidence: 98%
“…These Variants of Concern (VoC), named by the World Health Organization (WHO), have become widespread in the world replacing other lineages [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although major concerns have been raised on the emergence of Beta This will later cause functional instability in isolates, resulting in susceptible illnesses, and even an increase in the degree of pathogenicity [36]. In nations with poor containment capability, it was proven that the SARS-CoV-2 mutant lineage G (S-D614G) was able to replace earlier lineages more efficiently and was associated with a higher degree of disease severity [37]. Moreover, the emergence of more virulent strains such as VOC and VOI that harbored the D614G mutation in Spike protein suggests that D614G variant had constantly subjected to positive selection pressure.…”
Section: Discussionmentioning
confidence: 99%